Síntese, caracterização, estudos in silico e avaliação biológica de novos derivados da piperina - Costa, Normando Alexandre da Silva (2019)
Piperine is an alkaloid present in species of the genus Piper, this molecule has several biological activities, many of interest to the pharmaceutical industry, as an antitumor activity. Being a naturally occurring molecule, simple extraction with high yields. In this work, the synthesis and characterization of 15 amido esters derived from piperine have been described, all molecules being unpublished. The final products were obtained by a nucleophilic substitution reaction (SN2) between the salt of the pentafluoric acid and the substituted 2-chloroacetamides, in yields ranging from 63 to 92%. Confirmation of the structures was done using spectroscopic methods, such as IR, 1H and 13 C NMR and elemental analysis. The physico-chemical, toxicological, oral bioavailability, permeability by the blood-brain barrier, interactions with the enzyme Cytochrome p-450 and G-glycoprotein, both analyzes performed by in silico tests through free software (SwissAdme, Osiris and Molispiration). With the exception of the HE12 molecule, all molecules have adequate oral bioavailability. In the toxicological evaluation, the molecules presented reproductive risk, coming from the natural structure of piperine, the molecules HE03 and HE05 presented also irritant and tumorogenic risk respectively. In the microbiological evaluation of the molecules, the microdilution technique was used to obtain the minimum inhibitory concentrations of the microorganisms growth (MIC) against the following microorganisms pathogenic to humans: Staphylococcus aureus ATCC-13150; Staphylococcus epidermidis ATCC-12228; Pseudomonas aeruginosa ATCC-25853; Candida albicans - ATCC 76645, LM-1108, LM; Candida tropicalis ATCC 13803, LM 18 and Aspergillus flavus LM714. The results demonstrated that the compounds did not present biological activity up to the maximum concentration of 1024 μg/mL.The HE02 and HE03 derivatives were submitted to acute preclinical toxicity tests, the lethal dose (LD50) was estimated at 2000 mg / kg for HE02 and 5000 mg / kg for HE03 (did not cause death of mice). The compounds HE02 and HE03 showed significant in vivo antitumor activity in the Ehrlich Ascitic Carcinoma (CAE) model, especially considering the viability and total cell parameters, a significant decrease was observed in the animals treated with HE02 and HE03 at all experimental doses. There was no significant difference between the doses of 12.5 and 25 mg/kg of HE02 and HE03, presenting potent antitumor activity in vivo against CAE. In addition, HE03, in this tumor line and at concentrations of 6.25 and 12.5 mg/kg, reduced the evaluated parameters similar to 5- Fluorouracil, used as a positive control in this assay. Such news derivatives are important compounds for evaluation in in vivo tests.